Development of style in the writings of John Cowper Powys, 1915-1929 - Lock, C; Charles John Somerset Lock (1982)
﻿ Between 1915 and 1929 J.C. Powys wrote five novels, Wood and Stone, Rodmoor, After My Fashion, Ducdame, and Wolf Solent, and two unpublished plays, Paddock Calls and a dramatisation of Dostoievsky's The Idiot. To each of these seven works a single chapter is devoted. In addition, three short chapters fill in biographical details and bridge chronological gaps; their subjects are Powys' unpublished writings, his work as a dramatist, and his contacts with modernism. The latter chapter provides biographical support for the main critical contention of the thesis, Powys' central place in twentieth-century literature. Bach chapter describes the biographical context in which the novel or play was written, before proceeding with a textual analysis. The critical aim is to demonstrate Powys' technique, his consciousness of aesthetic and formal questions, and his style. Powys' ideas and beliefs are discussed only with reference to his style and form of expression. The broad development from Wood and Stone to Wolf Solent is seen and analysed in terms of an increasing sophistication of technique. Particular stress is laid on Powys' treatment of his protagonist's self-consciousness, culminating in the formal solution of Wolf Solent. As literary history, apart from placing Powys among contemporaries such as Joyce, Pound, Mann, Faulkner and Dreiser, the thesis shows the influence on Powys of Henry James, Turgenev, Hardy and others. The most important and most widely recognised influence, of Dostoievsky, is examined from critical and biographical angles. Incidentally to its main purpose, the thesis provides the most detailed biographical record, to date, of Powys' life in these years. Contemporary documentation has been used whenever possible, and extensively; much of it, mainly correspondence, is unpublished.